2015
DOI: 10.1177/1934578x1501000428
|View full text |Cite
|
Sign up to set email alerts
|

Hydropiperside, a new Sphingoglycolipid from Polygonum hydropiper

Abstract: One new sphingoglycolipid, hydropiperside, along with two known compounds, flaccidine and quercetin were isolated from the methanolic extract of Polygonum hydropiper. Elucidation of structures was achieved by NMR (1D and 2D) data, mass (EI and FAB) spectroscopy and chemical means.The genus Polygonum, family Polygonaceae, is comprised of about 60 species of annual or perennial herbs [1]. P. hydropiper Linn (syn. Persicaria hydropiper) is used in traditional medicine for many ailments like headache, liver enlarg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Phytochemical investigation of Polygonum hydropiper is essential from the point of economical, medicinal and biological importance. Earlier investigation on the medicinal plant Polygonum hydropiper, Linn, reported some drimane-type sesquiand nor sesquiterpenoids (Huq et al, 2014;Sultana et al, 2011;Haraguchi et al, 1992;Fukuyama et al, 1985Fukuyama et al, , 1982, flavonoid (Peng et al, 2003;Smolarz, 2002;Furuta et al, 1986), and recently, cerebroside (Sultana et al, 2015) type compounds have been isolated. It is also found that one report has been made on the phytochemical investigation of the Bangladeshi origin of this species.…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical investigation of Polygonum hydropiper is essential from the point of economical, medicinal and biological importance. Earlier investigation on the medicinal plant Polygonum hydropiper, Linn, reported some drimane-type sesquiand nor sesquiterpenoids (Huq et al, 2014;Sultana et al, 2011;Haraguchi et al, 1992;Fukuyama et al, 1985Fukuyama et al, , 1982, flavonoid (Peng et al, 2003;Smolarz, 2002;Furuta et al, 1986), and recently, cerebroside (Sultana et al, 2015) type compounds have been isolated. It is also found that one report has been made on the phytochemical investigation of the Bangladeshi origin of this species.…”
Section: Introductionmentioning
confidence: 99%